The effect of disease risk probability and disease type on interest in clinic-based versus direct-to-consumer genetic testing services - Sherman, Kerry; Shaw, Laura-Kate; Champion, Katrina; Caldeira, Fernanda; McCaskill, Margaret (Journal of behavioral medicine, 2015)
The effect of disease-specific cognitions on interest in clinic-based and direct-to-consumer (DTC) genetic testing was assessed. Participants (N = 309) responded to an online hypothetical scenario and received genetic testing-related messages that varied by risk probability (25, 50, 75 %) and disease type (Alzheimer’s disease vs. Type 2 Diabetes). Post-manipulation interest increased for both testing types, but was greater for clinic-based testing. Interest was greater for Type 2 Diabetes than for Alzheimer’s disease, the latter perceived as more severe and likely, and less treatable and preventable. For DTC testing only, participants allocated to the high risk condition (75 %) had greater testing interest than those in the low (25 %) category. DTC testing is perceived as a viable, but less preferred, option compared with clinic-based testing. Particularly when considering DTC genetic testing, there is a need to emphasize subjective disease-related perceptions, including risk probability.
Gesehen am 17.06.2020